THE EFFECT OF FINANCIAL RATIOS ON PROFIT GROWTH IN MINING COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE - Gembira Marbun (PT. Radja Intercontinental Publishing, 2026)
This study investigates the influence of financial ratios on the profit growth of mining companies listed on the Indonesia Stock Exchange (IDX) from 2017 to 2020. Specifically, it examines the impact of four financial ratios: Current Ratio (CR), Debt to Asset Ratio (DAR), Total Asset Turnover (TATO), and Return on Assets (ROA). A multiple linear regression analysis is employed to analyze the data. The findings reveal that each of the ratios significantly influences profit growth, both individually and collectively. The study highlights that CR, DAR, TATO, and ROA are essential indicators for assessing the financial health of mining companies and can predict future profit growth. These results are valuable for investors and creditors in making informed decisions regarding investments in the mining sector. The study contributes to the growing body of literature on financial performance analysis and offers practical insights for both researchers and industry professionals.